A taxonomic revision of the myrmecophilous genus Lomechusoides Tottenham, 1939 (Coleoptera: Staphylinidae: Aleocharinae) Part I. Redescription of the genus, definition of species groups and the revision of the amurensis Wasmann 1897 species group - Jászay, Tomáš; Hlaváč, Peter (Zootaxa, 2013)
The genus Lomechusoides Tottenham, 1939 is redescribed, the definition of species groups and the key to these groups is provided. The revision of the species group L. amurensis as well as the key to the identification of this group is given. The amurensis species group contains following species: L. amurensis (Wasmann 1897), L. kozlovi sp. nov., L. schneideri Mar-uyama & Hlaváč, 2005 and L. suensoni (Bernhauer 1936). The synonymy of L. ganglbaueri uralensis (Bernhauer 1936) to L. amurensis is confirmed. L. suensoni (Bernhauer, 1936) is revalidated as a good species from a synonymy of L. amu-rensis.